Bantuan Hukum Terhadap Anggota Polri Atas Pelanggaran Kode Etik Profesi Polri (KEPP) Sebagai Implementasi Pemenuhan Hak Hukum Dan Keadilan (Access to Law and Justice) - Fernando (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2022)
As a consequence of the violation of the Police code of ethics by members of the National Police, there is ethical responsibility in the session of the National Police Professional Code of Ethics Commission. Legal assistance in the form of assistance is the constitutional right of every citizen, including members of the National Police. The issuance of the Regulation of the Head of the National Police of the Republic of Indonesia Number 2 of 2017 concerning Procedures for Providing Legal Aid within the Police, should be a tangible manifestation of the responsibility of the National Police for legal rights and justice for members of the Indonesian National Police. This type of research is carried out using a normative juridical method, which is carried out by examining library materials or secondary data as a basis for research by conducting a search on regulations and literature related to the problems studied. That the enforcement of the Police Professional Code of Ethics must be carried out in an objective, accountable manner, upholding legal certainty and a sense of justice.